Умови виникнення ферорезонансних процесів в електричних мережах - Тугай, І. Ю. (Видавництво Національного університету «Львівська політехніка», 2007)
Ferroresonance in electrical power systems currently attracts a lot of attention. It is shown that ferroresonant circuit can be driven into chaotic behaviour.